Interplay Between Sub-Cellular Alterations of Calcium Release and T-Tubular Defects in Cardiac Diseases - Scardigli, Marina; Ferrantini, Cecilia; Crocini, Claudia; Pavone, Francesco S.; Sacconi, Leonardo (Frontiers in Physiology, 2018)
Asynchronous Ca2+ release promotes non-homogeneous myofilament activation, leading to mechanical dysfunction, as well as initiation of propagated calcium waves and arrhythmias. Recent advances in microscopy techniques allowed functional measurements in cardiac preparation with unprecedented spatial and temporal resolution. Ultra-fast deflectors were used to rapidly scan laser beams across the sample, performing optical measurements of local Ca2+ fluxes and action potential from multiple sites within cardiac cells. The capability of probing different sub-cellular domains simultaneously has opened promising perspectives for studying the variability of Ca2+ transient kinetics in space and time. This methodology has been found very useful also to unravel the spatiotemporal-relationship between local Ca2+ release and action potential propagation across the t-tubular system. For instance, in several cardiac disease models t-tubules fail to conduct action potential, accompanied with slower local Ca2+ transients as compared to regions with electrically coupled elements. By studying Ca2+ release at multiple sites simultaneously, a significant increment of variability (both in time and in space) has been also observed in these pathological settings. Interestingly, the increased variability does not directly correlate with the degree of morphological disruption nor with the occurrence of electrical defects, suggesting a role for other players of the excitation-contraction coupling machinery. In this manuscript, we will review sub-cellular alterations of Ca2+ release found in different pathological models and discuss their potential interplay with morpho-functional defects at t-tubular level.